Modulation of chemotherapeutic drug resistance in neuroblastoma SK‐N‐AS cells by the neural apoptosis inhibitory protein and miR‐520f. Issue 7 (2nd September 2014) - Harvey, Harry; Piskareva, Olga; Creevey, Laura; Alcock, Leah C.; Buckley, Patrick G; O'Sullivan, Maureen J.; Segura, Miguel F.; Gallego, Soledad; Stallings, Raymond L.; Bray, Isabella M.
<x xml:space="preserve">Abstract</x> The acquisition of multidrug resistance is a major impediment to the successful treatment of neuroblastoma, a clinically heterogeneous cancer accounting for ∼15% of all pediatric cancer deaths. The MYCN transcription factor, whose gene is amplified in ∼30% of high‐risk neuroblastoma cases, influences drug resistance by regulating a cadre of genes, including those involved with drug efflux, however, other high‐risk subtypes of neuroblastoma lacking MYCN amplification, such as those with chromosome 11q deletions, also acquire multidrug resistance. To elucidate additional mechanisms involved with drug resistance in non‐MYCN amplified tumour cells, an SK‐N‐AS subline (SK‐N‐AsCis24) that is significantly resistant to cisplatin and cross resistant to etoposide was developed through a pulse‐selection process. High resolution aCGH analysis of SK‐N‐AsCis24 revealed a focal gain on chromosome 5 containing the coding sequence for the neural apoptosis inhibitory protein (NAIP). Significant overexpression of NAIP mRNA and protein was documented, while experimental modulation of NAIP levels in both SK‐N‐AsCis24 and in parental SK‐N‐AS cells confirmed that NAIP was responsible for the drug resistant phenotype by apoptosis inhibition. Furthermore, a decrease in the NAIP targeting microRNA, miR‐520f, was also demonstrated to be partially responsible for increased NAIP levels in SK‐N‐AsCis24. Interestingly, miR‐520f levels were determined to be significantly lower in postchemotherapy treatment tumours relative to matched prechemotherapy samples, consistent with a role for this miRNA in the acquisition of drug resistance in vivo, potentially through decreased NAIP targeting. Our findings provide biological novel insight into neuroblastoma drug‐resistance and have implications for future therapeutic research.